Salivary secretory immunoglobulin A response of elite speed skaters during a competition period - Kon, M.; Iizuka, T.; Maegawa, T.; Hashimoto, E.; Yuda, J.; Aoyanagi, T.; Akimoto, T.; Takahashi, H. (The Journal of Strength and Conditioning Research, 2010)
We aimed to determine the responses of salivary secretory immunoglobulin A (SIgA) and the incidence of upper respiratory tract infections (URTI) symptoms among elite speed skaters during an actual competition period. The subjects were 8 international-class elite speed skaters. Saliva samples were obtained 3, 2, and 1 days before the race, the day of the race, and 1 day after the race. Salivary secretory immunoglobulin A concentration was measured by enzyme immunoassay, and SIgA secretion rate was calculated. A visual analogue scale was used to subjectively assess fatigue and tension. Daily URTI symptoms were recorded by using a questionnaire. There was no statistically significant difference in the saliva flow rate (p = 0.69), SIgA concentration (p = 0.07), and subjective fatigue (p = 0.07) during the competition period. The SIgA secretion rate recorded for the day of the race was significantly high compared with that of 3 and 2 days before and 1 day after the race (p < 0.05). The subjective tension recorded on the race day was significantly high compared with that for 3, 2, and 1 days before the race (p < 0.05). Two subjects exhibited URTI symptoms after the race. These findings suggest that salivary SIgA in elite speed skaters increased after a tapering period and that an actual high-intensity speed skating race decreased salivary SIgA in elite speed skaters. These data also suggest that the incidence of URTI symptoms might be related to the SIgA level. Coaches may need to take precautions after competitions to minimize their athletes' contact with cold viruses and adjust training load for a few days after competition to improve the decreased mucosal immune function.